Interview: Reflections on pain research and management: past, present and future. (May 2011) - Chapman, C Richard
C Richard Chapman is Professor and Director of the Pain Research Center in the department of Anesthesiology at the University of Utah, Salt Lake City (UT, USA). A psychologist and psychophysiologist, he has worked in the pain research field since 1970. He spent 29 years at the University of Washington before coming to the University of Utah. His interests span acute pain, chronic pain, cancer pain and pain measurement.